Halal Tourism Development Strategy through Baitul Muamalat: A Case Study - Khaerunnisa, Nurcahya; Nawawi, Muhammad Kholil; Gustiawati, Syarifah (SMART Insight, 2024)
Tourism is a sector that has the potential to be developed as a source of regional income. The tourist destination development program is expected to provide income for economic development. Tegalwaru is an example of a rural tourist village located in the Ciampea sub-district, Bogor Regency. This village is famous as a home for various agricultural production and entrepreneurship. Tegalwaru's rural tourism potential needs to be further developed to attract more tourists to visit the village. Waru Farm Land is the first Indonesian traditional Islamic residential and tourism area in Indonesia. The potential of Waru Farm Land as a halal tourist destination is very large because its concept is Islamic and centered on the Muslim community. This research aims to explain the development strategy for managing Waru Farm Land. In this research, the author used a qualitative research method with a descriptive approach and purposive sampling. Data collection techniques include observation, interviews, and documentation. The results of this research are, that Waru Farm Land's conditions include Islamic attractions such as the Prophet's Sunnah, such as horse riding, archery, swimming, mini zoo, and painting activities. The tourism development strategy carried out by Waru Farm Land is through online and offline promotions. The supporting factors are the condition of the area which is still beautiful with a wealth of natural resources and is located in an MSME tourist village, human resources supported by the majority of the local community who are Muslim, and support from the Ciampea District Government, as well as inhibiting factors namely road accessibility to the location and lack of knowledge of the community about halal tourism. community about halal tourism.